Heading and head injuries in soccer - Kirkendall, D. T.; Jordan, S. E.; Garrett, W. E. (Sports Medicine, 2001)
In the world of sports, soccer is unique because of the purposeful use of the unprotected head for controlling and advancing the ball. This skill obviously places the player at risk of head injury and the game does carry some risk. Head injury can be a result of contact of the head with another head (or other body parts), ground, goal post, other unknown objects or even the ball. Such impacts can lead to contusions, fractures, eye injuries, concussions or even, in rare cases, death. Coaches, players, parents and physicians are rightly concerned about the risk of head injury in soccer. Current research shows that selected soccer players have some degree of cognitive dysfunction. It is important to determine the reasons behind such deficits. Purposeful heading has been blamed, but a closer look at the studies that focus on heading has revealed methodological concerns that question the validity of blaming purposeful heading of the ball. The player's history and age (did they play when the ball was leather and could absorb significant amounts of water), alcohol intake, drug intake, learning disabilities, concussion definition and control group use/composition are all factors that cloud the ability to blame purposeful heading. What does seem clear is that a player's history of concussive episodes is a more likely explanation for cognitive deficits. While it is likely that the subconcussive impact of purposeful heading is a doubtful factor in the noted deficits, it is unknown whether multiple subconcussive impacts might have some lingering effects. In addition, it is unknown whether the noted deficits have any affect on daily life. Proper instruction in the technique is critical because if the ball contacts an unprepared head (as in accidental head-ball contacts), the potential for serious injury is possible. To further our understanding of the relationship of heading, head injury and cognitive deficits, we need to: learn more about the actual impact of a ball on the head, verify the exposure to heading at all ages and competitive levels, determine stable estimates of concussive injury rates across the soccer spectrum, conduct prospective longitudinal studies on soccer players focusing on exposure, injury and cognition, and determine the minimum safe age to begin instruction on the skill of heading. Only then will we be able to speak with some authority on the issue of heading and head injuries in soccer.